Post-traumatic Growth in the Link with Resilience, Self-compassion, and the Personal and Clinical Characteristics in Adolescents with Life-threatening Disease: A Cross-sectional Correlational Study - Zahra Ghasemi; Manijeh Nourian; Azam Shirinabadi Farahani; Amir Heidari; Maliheh Nasiri (International Journal of Community Based Nursing and Midwifery)
Background: Post-traumatic growth (PTG) is a significant factor influencing health outcomes. This research aims to determine the status of PTG and its correlation with resilience, self-compassion (SC) and personal and clinical characteristics in adolescents with life-threatening diseases.Methods: In this cross-sectional correlational study, 200 adolescents with life-threatening disease who were referred to clinics or hospitalized at Shohada Tajrish and children’s Medical Center hospitals from June to October 2023 in Tehran, Iran, were selected through convenience sampling. Data was collected using personal and clinical characteristics form, PTG Inventory, resilience scale, and SC scale. Analysis was conducted using SPSS software version 20, employing descriptive statistics, Pearson’s correlation coefficient, ANOVA, t-tests, and multiple linear regression analysis with a P value≤0.05.Results: The study found that the mean total PTG score was 63.35±18.19, the resilience score was 82.39±13.62, and the SC score was 76.36±6.65. There was a significant difference between various treatment stages in the total PTG score (P=0.05), and PTG score was correlated with resilience (r=0.63, P<0.001) and SC score (r=0.20, P=0.04). The total resilience score was the sole predictor of the total PTG score. Higher resilience total scores during chemotherapy and radiotherapy (B=0.74, P<0.001), surgery (B=1.08, P<0.001), and drug treatment phases (B=0.89, P<0.001), were associated with higher PTG scores. While SC was positively correlated with PTG, it did not predict it (P>0.05).Conclusion: The study suggests that enhancing resilience in adolescents with life-threatening diseases can improve PTG. Future studies are recommended to explore the impact of resilience strategies training on PTG in this population.